2008
DOI: 10.1590/s0034-72802008000600007
|View full text |Cite
|
Sign up to set email alerts
|

Axenfeld-Rieger anomaly and corneal endothelial dystrophy: a case series

Abstract: Report of a study of a family with a remarkable combination of endothelial corneal dystrophy, and anterior chamber dysgenesis classified as Axenfeld-Rieger anomaly. A 56 year-old female had blurred vision complaints. A slit lamp evaluation showed a bilateral posterior embryotoxon and guttata with corneal edema, Descemet membrane's folds, characterizing Fuchs endothelial dystrophy. A 27 year-old daughter was asymptomatic. The biomicroscopic exam disclosed a bilateral nasal and temporal posterior embryotoxon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…1,4 Kniestedt C et al 5 investigated the association of AXRA with Fuchs endothelial corneal dystrophy and reported the appearance of beaten metal due to excrescences in Descemet membrane on histological evaluation. Oliveira et al 6 also reported features of corneal endothelial dystrophy in a family with AXRA. Developmentally, the trabecular meshwork and corneal endothelium share a common pathway during embryogenesis, and it is possible that the corneal endothelium might also be affected in addition to the angle abnormalities.…”
mentioning
confidence: 88%
“…1,4 Kniestedt C et al 5 investigated the association of AXRA with Fuchs endothelial corneal dystrophy and reported the appearance of beaten metal due to excrescences in Descemet membrane on histological evaluation. Oliveira et al 6 also reported features of corneal endothelial dystrophy in a family with AXRA. Developmentally, the trabecular meshwork and corneal endothelium share a common pathway during embryogenesis, and it is possible that the corneal endothelium might also be affected in addition to the angle abnormalities.…”
mentioning
confidence: 88%